The morphology and phonology of exponence - Trommer, Jochen (Oxford : Oxford University Press, 2012)
Addressing the common problems, questions and solutions of exponence, this book contains contributions from leading specialists who formulate a coherent research programme which integrates the central insights of the last decades and provides challenges for the future.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grammar, Comparative and general -- Morphosyntax; Grammar, Comparative and general -- Phonology; Typology (Linguistics)